Zina in the Digital Era: New Challenges for the Enforcement of Islamic Criminal Law - Farhan Fathur Rahman; Rahma Fitri Amelia Hasibuan; Dinda Ayu Arini Chaniago; M. Rangga Syahputra Saragih; Annisa Putri Andini Tanjung (ISNU Nine-Star Multidisciplinary Journal, 2026)
This paper examines the transformation of zina in the digital era and its implications for the enforcement of Islamic criminal law. The background of the study is rooted in the emergence of technology-mediated sexual practices such as sexting, cybersex, and the online dissemination of intimate content that challenge the classical fiqh conception of zina as a physical act subject to strict ḥudūd evidentiary standards. Using a qualitative normative-empirical research method, the study analyzes classical fiqh sources, contemporary legal literature, and documented digital practices. The research stages include problem identification, literature review, data collection on digital behaviors, analysis through maqāṣid al-sharīʿah and ijtihād frameworks, and synthesis of findings. The results show a significant juridical gap between traditional evidentiary mechanisms and digitally mediated sexual misconduct, compounded by issues of digital evidence reliability, jurisdiction, and privacy protection. The discussion highlights both the enduring relevance and structural limitations of classical evidentiary paradigms, underscoring the need for adaptive, multidimensional legal approaches within Islamic criminal law.